1995
DOI: 10.1017/s1355617700000230
|View full text |Cite
|
Sign up to set email alerts
|

The HNRC 500-Neuropsychology of Hiv infection at different disease stages

Abstract: The present study examined neuropsychological (NP) functioning and associated medical, neurological, brain magnetic resonance imaging (MRI), and psychiatric findings in 389 nondemented males infected with Human Immunodeficiency Virus-Type 1 (HIV-1), and in 111 uninfected controls. Using a comprehensive NP test battery, we found increased rates of impairment at each successive stage of HIV infection. HIV-related NP impairment was generally mild, especially in the medically asymptomatic stage of infection, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
530
4
14

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 602 publications
(600 citation statements)
references
References 77 publications
(73 reference statements)
46
530
4
14
Order By: Relevance
“…The ratings procedure utilized in this study has undergone extensive evaluation, and inter-rater reliability has been found to be excellent. The rationale, nature, reliability and validity of these ratings have been described in detail elsewhere (Heaton et al, , 1994a(Heaton et al, , 1994b(Heaton et al, , 1995.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratings procedure utilized in this study has undergone extensive evaluation, and inter-rater reliability has been found to be excellent. The rationale, nature, reliability and validity of these ratings have been described in detail elsewhere (Heaton et al, , 1994a(Heaton et al, , 1994b(Heaton et al, , 1995.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
“…HIV-infection can be associated with CNS involvement and changes in neurobehavioral status, particularly in advanced stages of the illness (Bornstein et al, 1992;Grant et al, 1987;Heaton et al, 1995;Stern et al, 1991). Neuroimaging and neuropsychological (NP) studies suggest initial preferential involvement of frontostriatal circuitries, reduction in white matter volumes, and a spotty pattern of mild NP impairments, with increasing structural abnormalities and NP impairment as HIV disease state advances (Heaton et al, 1995;Jernigan et al, 1993;Stout et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined 235 HIV-infected and 56 HIVuninfected community-dwelling adults recruited by the HIV Neurobehavioral Research Program (HNRP) for various cohort studies described elsewhere [42][43][44]. Inclusion criteria for present analyses included having at least two visits with data for both self-reported PA and global neurocognition.…”
Section: Participantsmentioning
confidence: 99%
“…Methamphetamine (METH) abuse can induce neuronal dysfunction and CNS pathology, often in subcortical regions of the brain (Seiden and Ricaurte, 1987;Woolverton et al, 1989;Heaton et al, 1995;Hall et al, 1996;Kieburtz et al, 1996). To date, most studies involving METH administration and the consequent CNS pathology have focused on neurotoxicity in the striatal dopamine projections (Ricaurte et al, 1984;Cadet et al, 1998;Villemagne et al, 1998;Harvey et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%